2011
DOI: 10.1128/jb.01460-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of CdgB, a Diguanylate Cyclase Involved in Developmental Processes in Streptomyces coelicolor

Abstract: We describe the identification and functional characterization of cdgB (SCO4281), a recently discovered target of BldD, a key regulator of morphological differentiation and antibiotic production in the mycelial bacteria of the genus Streptomyces. cdgB (cyclic dimeric GMP [c-di-GMP] B) encodes a GGDEF-containing protein that has diguanylate cyclase activity in vitro. Consistent with this enzymatic activity, heterologous expression of cdgB in Escherichia coli resulted in increased production of extracellular mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 46 publications
5
62
0
Order By: Relevance
“…Our study, along with those of Buttner and colleagues (17,59), reveals an apparently conserved function of c-di-GMP signaling in modulation of development in actinomycetes. This extends the realm of processes controlled by c-di-GMP and suggests that future studies in the Gram-positive bacteria may result in new, yet-unanticipated processes controlled by this second messenger, new kinds of c-di-GMP receptors, and new regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our study, along with those of Buttner and colleagues (17,59), reveals an apparently conserved function of c-di-GMP signaling in modulation of development in actinomycetes. This extends the realm of processes controlled by c-di-GMP and suggests that future studies in the Gram-positive bacteria may result in new, yet-unanticipated processes controlled by this second messenger, new kinds of c-di-GMP receptors, and new regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…Recent experiments by the Buttner group showed that overexpression of S. coelicolor DGCs encoded by cdgA or cdgB (SCO4281) block aerial mycelium formation (17,59), i.e., produce the same bald phenotype as does the rmdA rmdB double mutant. It is likely that RmdA and RmdB counterbalance the effects of CdgA and CdgB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of yet another DGC, CdgB (SCO4281), resulted in the impaired formation of aerial mycelium. It is peculiar that the cdgB deletion also showed impaired hypha formation (323). Two EAL domain PDEs, RmdA (SCO0928) and RmdB (SCO5495), were also identified as responsible for hypha formation.…”
Section: Regulation Of Cell Cycle and Differentiationmentioning
confidence: 99%
“…The first diguanylate cyclase identified in Gram-positive bacteria was Mycobacterium smegmatis MSDGC-1, a protein with both DGC activity and PDE activity in vitro (17,18). More recently, additional c-di-GMP signaling components have been characterized in M. smegmatis (19), Mycobacterium tuberculosis (20), Streptomyces coelicolor (21)(22)(23), and Clostridium difficile (15,16,24,25). These studies establish c-di-GMP as a secondary messenger in Gram-positive bacteria, but until recently the possibility of c-di-GMP signaling in a widely studied Gram-positive model organism, Bacillus subtilis, had not been reported (26).…”
mentioning
confidence: 99%